PROPOSAL OF METHOD OF EVALUATING LOCATION RISK OF WELFARE FACILITIES IN DISASTER - T. Nagaie; A. Tanoue; K. Hokao; T. Inohae; H. F. Li (International Association of Lowland Technology, 2011)
At the disaster, special consideration is necessary for vulnerable people, the place in which they gather is dangerous. Therefore, it is necessary to think about disaster prevention and the disaster mitigation measures that vulnerable people can live safely. And it pays attention to the location place of the welfare facility and the method of evaluating the location risk of the welfare facility in the disaster is examined It pays attention to the characteristic of the welfare facility manager in facilities, people in facilities and person who lives in the vicinity of facilities. It aims to think disaster prevention and disaster mitigation measures. The present study did the analysis and the site investigation by GIS and, in addition, executed the hearing investigation to the object municipality. Moreover, the evaluated space level was set, the disaster location risk of each space level was evaluated, and consideration and the examination of the evaluation examined disaster prevention and the disaster mitigation measures furthermore. The method of evaluating five was made for the earthquake flood damage and the sediment disaster. The method of evaluating five was applied to the vicinity of the welfare facilities of Saga City, and it evaluated it. As a result, it has understood the location in a dangerous place in view of the disaster. The problem of examination of safety for the life after it had taken shelter as a disaster mitigation measures not to expand disaster of it arose.